Nepal-USA Diplomatic Relations (April 25, 1947): A Historical Overview (NPRC Journal of Multidisciplinary Research, 2026)
Background: Most Rana Prime Ministers restricted Nepal's foreign policy to relations with Britain alone. However, Prime Minister Padma Shumsher Rana, initiated a policy shift toward expanding diplomatic ties with other nations.Objective: This article examines the circumstances leading to the establishment of Nepal-US diplomatic relations on April 25, 1947 the mutual interest of both countries and the provisions of the Treaty of Commerce and Friendship.Methods: The research employs qualitative historical methodology using descriptive and Analytical approaches drawing from primary and secondary sources including government documents, Academic books, articles and contemporary newspaper (Gorkhapatra). Gregorian (A.D.) and Bikram Sambat (B.S.) date systems are used in the main text of the books, journals, news papers etc. However, A.D. has not mentioned in English dates and B.S. has been referred in Nepali dates.Key Findings: The Treaty of Commerce and Friendship (12 articles) established diplomatic relations based on equality.  Key events included the presentation of the US ‘Legion of Merit’ to Prime Minister Padma Shamsher (November 1946) and Joseph C.  Satterthwaite’s arrival as President Truman's special representative (April 1947).  Nepal sought to preserve Rana Rule amid anticipated British withdrawal from India, while the US aimed to prevent communist expansion in South Asia.Conclusion: While the Rana rulers political objectives remained unfulfilled (the US did not support them during the 1951 Anti-Rana revolution), The US successfully achieved its goal of containing communist influence.  the Treaty remains active with no termination notice to date.